2008
DOI: 10.1007/s11701-008-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic robotic-assisted gastrointestinal surgery: a Geneva experience

Abstract: The continuing development of robotic surgery supports its use in laparoscopic gastrointestinal surgery. Our study retrospectively reviewed the surgical outcome and patient's satisfaction of gastrointestinal laparoscopic robotic procedures. From January 2003 to September 2007, 94 patients (27 women, 67 men) with a mean age of 53 years (range 19-84 years) underwent laparoscopic surgery with a da Vinci robotic system. There were 40 colorectal cases (43%), 31 anti-reXux surgery cases (33%) and 14 obesity surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…In total 20 studies fulfilled the inclusion criteria and were included in this review. Fourteen studies were case series, one of which was also a comparative study with conventional laparoscopy . Three were case control studies , two comparative nonrandomized trials and one study was a retrospective analysis of prospectively collected data .…”
Section: Resultsmentioning
confidence: 99%
“…In total 20 studies fulfilled the inclusion criteria and were included in this review. Fourteen studies were case series, one of which was also a comparative study with conventional laparoscopy . Three were case control studies , two comparative nonrandomized trials and one study was a retrospective analysis of prospectively collected data .…”
Section: Resultsmentioning
confidence: 99%
“…Following careful screening, all 22 primary studies met the inclusion criteria. These included one randomized controlled trial7, three prospective cohort studies14–16, 18 case‐series17–34. Six of the included studies involved restrictive bariatric procedures, thirteen studies involved malabsorptive procedures and three involved both.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reports have also demonstrated that robotic left colectomy and sigmoid resection are technically feasible and safe . A list of retrospective studies comparing the efficacy of robotic with laparoscopic sigmoid or left colectomy is summarized in Table .…”
Section: Discussionmentioning
confidence: 99%